Utilization of CMS pre-ESRD Kidney Disease Education services and its associations with the home dialysis therapies. Issue 5 (September 2021) - Shukla, Ashutosh M; Bozorgmehri, Shahab; Ruchi, Rupam; Mohandas, Rajesh; Hale-Gallardo, Jennifer L; Ozrazgat-Baslanti, Tezcan; Orozco, Tatiana; Segal, Mark S; Jia, Huanguang
Background: Kidney Disease Education (KDE) has been shown to improve informed dialysis selection and home dialysis use, two long-held but underachieved goals of US nephrology community. In 2010, the Center for Medicare and Medicaid Services launched a policy of KDE reimbursements for all Medicare beneficiaries with advanced chronic kidney disease. However, the incorporation of KDE service in real-world practice and its association with the home dialysis utilization has not been examined. Methods: Using the 2016 US Renal Data System linked to end-stage renal disease (ESRD) and pre-ESRD Medicare claim data, we identified all adult incident ESRD patients with active Medicare benefits at their first-ever dialysis during the study period (1 January 2010 to 31 December 2014). From these, we identified those who had at least one KDE service code before their dialysis initiation (KDE cohort) and compared them to a parsimoniously matched non-KDE control cohort in 1:4 proportions for age, gender, ESRD network, and the year of dialysis initiation. The primary outcome was home dialysis use at dialysis initiation, and secondary outcomes were home dialysis use at day 90 and anytime through the course of ESRD. Results: Of the 369, 968 qualifying incident ESRD Medicare beneficiaries with their first-ever dialysis during the study period, 3469 (0.9%) received KDE services before dialysis initiation. African American race, Hispanic ethnicity, and the presence of congestive heart failure and hypoalbuminemia were associated with significantly lower odds of receiving KDE services. Multivariate analyses showed that KDE recipients had twice the odds of initiating dialysis with home modalities (15.0% vs. 6.9%; adjusted odds ratio (aOR):95% confidence interval (CI) 2.0:1.7–2.4) and had significantly higher odds using home dialysis throughout the course of ESRD (home dialysis use at day 90 (17.6% vs. 9.9%, aOR:CI 1.7:1.4–1.9) and cumulatively (24.7% vs. 15.1%, aOR:CI 1.7:1.5–1.9)). Conclusions: Utilization of pre-ESRD KDE services is associated with significantly greater home dialysis utilization in the incident ESRD Medicare beneficiaries. The very low rates of utilization of these services suggest the need for focused systemic evaluations to identify and address the barriers and facilitators of this important patient-centered endeavor.